Long non-coding RNA HAGLROS facilitates tumorigenesis and progression in hepatocellular carcinoma by sponging miR-26b-5p to up-regulate karyopherin α2 (KPNA2) and inactivate p53 signaling. Issue 3 (1st March 2022) - Tang, Gaofeng; Zhao, Huibo; Xie, Zhantao; Wei, Sidong; Chen, Guoyong
ABSTRACT: Hepatocellular carcinoma (HCC) is a principal histologic type of liver cancer with high mortality. Long non-coding RNAs (LncRNAs) exert a crucial role in the pathogenesis of human tumors. To date, the functions and mechanisms of lncRNA HAGLROS in HCC are rarely reported. In the current study, HAGLROS exhibited a higher level in HCC tissues and cells. HAGLROS expression was positively correlated with tumor size, TNM stage and poor clinical prognosis. Loss-of-function experiments showed that knockdown of HAGLROS significantly lowered cell proliferation, cell cycle progression, migration, invasion and epithelial to mesenchymal transition (EMT) but induced apoptosis in vitro . Consistently, tumor growth in the nude mice was effectively slowed by the depletion of HAGLROS. Mechanistically, HAGLROS could competitively bind to miR-26b-5p to prevent the suppression of miR-26b-5p on its downstream target gene Karyopherin α2 (KPNA2). Moreover, the inhibitory effects of HAGLROS knockdown on cell malignant behaviors were reversed due to the miR-26b-5p down-regulation or KPNA2 overexpression. It was interesting to note that HAGLROS inactivated p53 signaling through targeting miR-26b-5p/KPNA2. In conclusion, our results demonstrated that HAGLROS contributed to the malignant progression of HCC via serving as a sponge for miR-26b-5p to facilitate KPNA2 expression and inactivate p53 signaling. Targeting HAGLROS/miR-26b-5p/KPNA2 axis might be an alternative therapeutic strategy for HCC patients. Graphical Abstract: uf0001